The evolution of brain death criteria: From historical foundations to modern standards. - Varon, Joseph; Hussaini, Najia; Nanlohy, Simon (Critical Care & Shock, 2025)
The concept of brain death, or death by neurologic criteria (BD/DNC), marks a transformative shift in defining death, moving from traditional cardiorespiratory cessation to neurological criteria driven by advancements in critical care and organ transplantation. This manuscript traces the evolution from 1950s European observations and the 1968 Harvard Committee report to the 1981 Uniform Determination of Death Act (UDDA) and the 2023 AAN/AAP/CNS/SCCM consensus guidelines. It explores historical milestones, modern clinical protocols, ancillary testing, and ongoing controversies, including the whole brain versus brainstem debate, ethical issues in organ donation, and cultural and religious objections. Emphasizing scientific rigor and interdisciplinary perspectives, this review advocates for global standardization while addressing critiques that brain death conflates dying with death.